2007
DOI: 10.1002/ijc.22679
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia can induce c‐Met expression in glioma cells and enhance SF/HGF‐induced cell migration

Abstract: The c-Met receptor and its ligand scatter factor/hepatocyte growth factor (SF/HGF) are strongly overexpressed in malignant gliomas. Signaling through c-Met as well as exposure to hypoxia can stimulate glioma cell migration and invasion. In several cancer cell types, hypoxia was shown to activate the c-met promoter, which contains hypoxia inducible factor-1 (HIF-1) binding sites. We hypothesized that hypoxia might upregulate c-Met also in glioma cells. Analyzing 18 different glioblastoma cell lines and 10 gliob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 47 publications
7
98
1
Order By: Relevance
“…Recent studies have shown that HIF-1α is widely found in all histiocytes, as well as in peripheral leukocytes (3,15,16). Moreover, increased HIF-1α expression occurs in a variety of solid tumor cells and stromal cells, which may be related to their migration and adhesion (17,18). In the current study, HIF-1α mRNA and protein expression in acute leukemia hBMSCs were significantly increased compared to control, suggesting that HIF-1α may have been involved in the formation of the leukemia bone marrow hypoxic microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that HIF-1α is widely found in all histiocytes, as well as in peripheral leukocytes (3,15,16). Moreover, increased HIF-1α expression occurs in a variety of solid tumor cells and stromal cells, which may be related to their migration and adhesion (17,18). In the current study, HIF-1α mRNA and protein expression in acute leukemia hBMSCs were significantly increased compared to control, suggesting that HIF-1α may have been involved in the formation of the leukemia bone marrow hypoxic microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…127 Hypoxia has been shown to upregulate c-Met expression, which enhances scatter factor/hepatocyte growth factor-induced cell migration. 128 In addition to MMPs, other studies have identified the protease cathepsin B as an important mediator of ECM degradation secreted by gliomas.…”
Section: Molecular Biology Of Glioma Invasionmentioning
confidence: 99%
“…21 HIF-1 is a known activator of c-MET in many cell types, including gliomas, and is thought to play a role in their invasiveness. 8,13 This reduced c-MET activity may explain the lack of invasion that we observed in the HIF-1a knock-down mice (data not shown). Although the cell line that we used has been criticized for its reduced invasive properties in our intracranial model, it does express scatter factor/hepatocyte growth factor (SF/ HGF) and c-MET.…”
mentioning
confidence: 74%